URGENSI PENDIDIKAN NILAI BAGI SISWA GEN ALPHA PADA ERA GLOBALISASI DI SEKOLAH DASAR - Abidin, Zainal; Audy Mita Melina; Novita fitriana (STAI Nusantara Banda Aceh, 2025)
Value-based education plays a crucial role in shaping the character of students, especially Generation Alpha who are growing up in the digital and globalized era. This generation is highly familiar with technology from an early age, influencing their behavior, learning styles, and value systems. Globalization brings both opportunities and challenges, such as moral decline, misuse of technology, and a decrease in social empathy. Therefore, value education in elementary schools is essential to equip students with moral principles, digital ethics, and national identity. This study employs a descriptive qualitative approach through literature review, analyzing educational regulations, books, and relevant scholarly articles. The findings indicate that character education strategies must be contextual and tailored to the characteristics of Generation Alpha. Effective approaches include role modeling, the use of digital media and visual storytelling, and the integration of Islamic values and developmental psychology. Teachers play a key role as facilitators and role models in shaping students’ character. In conclusion, value education should be an integral part of the elementary education process. Its implementation requires collaboration among teachers, parents, and the social environment to nurture a generation that is morally grounded, has strong integrity, and is adaptable to global changes.